2021
DOI: 10.3233/jad-210489
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Chemokines Expression Variations and Their Receptors in APP/PS1 Mice

Abstract: Background: In Alzheimer’s disease (AD), an increase in inflammation is distinctive. Amyloid precursor protein plus presenilin-1 (APP/PS1 mice) is a model for this illness. Chemokines secreted by central nervous system (CNS) cells could play multiple important roles in AD. Data looking for the chemokines involved in inflammatory mechanisms are lacking. To understand the changes that occur in the inflammation process in AD, it is necessary to improve strategies to act on specific inflammatory targets. Objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…In APP/PS1 mice, increased expression of CCL2 and CCR2 produced amyloidosis. The deficiency of CCL2 and CCR2 is followed by reduced Aβ phagocytosis and amyloid clearance (Jorda et al, 2021). In the early stage of AD pathology, microglia also release insulin-degrading enzyme (IDE), proteins of the matrix metalloproteinase 9 (MMP9), plasminogen and neprilysin, which are involved in Aβ degradation and induce Aβ clearance (Gao et al, 2018;Corraliza-Gómez et al, 2022).…”
Section: Clearance or Aggravation Of Aβmentioning
confidence: 99%
“…In APP/PS1 mice, increased expression of CCL2 and CCR2 produced amyloidosis. The deficiency of CCL2 and CCR2 is followed by reduced Aβ phagocytosis and amyloid clearance (Jorda et al, 2021). In the early stage of AD pathology, microglia also release insulin-degrading enzyme (IDE), proteins of the matrix metalloproteinase 9 (MMP9), plasminogen and neprilysin, which are involved in Aβ degradation and induce Aβ clearance (Gao et al, 2018;Corraliza-Gómez et al, 2022).…”
Section: Clearance or Aggravation Of Aβmentioning
confidence: 99%
“…Bijay ( 68 ) found that CCL11 significantly promoted the migration of glial cells and induced glial cells to produce reactive oxygen species by upregulating nicotinamide adenine dinucleotide phosphate oxidase 1 (NOX1), which eventually led to neuronal death. In addition, the study shows that the expression of CCL11/CCR3 is very likely to be an important factor involved in the inflammatory induction and demyelination of AD ( 6 ). In this present study, the content of CCL11 in the plasma and brain of the 5xFAD mice was detected for the first time, and it was found that QFY reversed the excessive level of CCL11 in the brain and plasma of the 5xFAD mice.…”
Section: Discussionmentioning
confidence: 99%
“…Through the genetic research on the families of patients with AD, the researchers found three main pathogenic genes, namely, β-amyloid precursor protein (APP) gene, presenilin 1 (PS1) gene, and presenilin 2 (PS2) gene, which laid the foundation for the formation of Aβ to play an important role in the pathogenesis of AD ( 5 ). Microglia are activated by Aβ and then release cytokines, chemokines, and other neurotoxic substances (such as NO and superoxide), which lead to neuroinflammation in the brain of AD patients ( 6 ). The 5xFAD mice express gene APP with mutation K670N/M671L (Swedish), I716V (Florida), and V717I (London) and PS1 with mutation M146L and L286V.…”
Section: Introductionmentioning
confidence: 99%
“…Protein extracts from quadriceps were mixed with equal volumes of SDS buffer (0.125 M Tris-HCl, pH 6.8, 2% SDS, 0.5% (v/v) 2-mercaptoethanol, 1% protease inhibitors, 1% bromophenol blue and 19% glycerol) and then boiled for five minutes. Protein concentration was determined using a modified Lowry method [ 26 ]. Proteins were separated using SDS-PAGE gels and transferred to polyvinylidene difluoride membranes.…”
Section: Methodsmentioning
confidence: 99%